Sentire animale? Trans-specismo e antropocentrismo fra cinema e tecnologie immersive - Conte, Pietro; Pinotti, Andrea (Scenari, 2024)
Is it possible to access the experiential worlds of other animal species? From Uexküll’s “soap bubble” theory to Nagel’s inaccessible bats, both biology and philosophy have categorically denied that such a gateway to the Animal is passable. Yet, paradoxically enough, Uexküll himself did nothing but try, imagining the subjective worlds of animals and resorting to drawings and photographs to support this imagination. Cinema and virtual reality have taken up and relaunched this challenge. This article examines some relevant case studies, reflecting on the human, all-too-human desire to transcend the human itself. It aims to distinguish between two different types of first-person shots – anthropomorphic and theriomorphic – used to represent non-human modes of perception.